Respuesta :

Answer:

(-2,3)

Step-by-step explanation:

4x+5y =7

y = 3x+9

Substitute the second equation into the first equation

4x +5(3x+9) = 7

Distribute

4x + 15x + 45 = 7

Combine like terms

19x +45 =7

Subtract 45 from each side

19x +45-45 = 7-45

19x = -38

Divide by 19

19x/19 = -38/19

x = -2

Now we need to find y

y = 3x+9

Putting in x=-2

y = 3(-2) +9

y = -6 +9

y = 3

(-2,3)

Answer:

x = - 2

y = 3

Step-by-step explanation:

First name these 2 equations with 1 and 2.

4x + 5y = 7 (1)

y = 3x + 9 (2)

Since y is already isolated in (2), so we can skip the isolation step and continue to substitute.

Substitute (2) into (1).

4x + 5(3x+9) = 7

Expand.

4x + 15x + 45 = 7

Group.

19x + 45 = 7

Shift +45 to the other side and turn it into -45.

19x = 7 - 45

19x = -38

Shift x19 to the other side, turn it into /19.

X = - 38/19

X = - 2

Now we solved x already, we can just substitute x= - 2 back to equation (2).

y = 3(-2) + 9

y = - 6 + 9

y = 3

So, the answers are

x = - 2

y = 3